2008
DOI: 10.2106/jbjs.g.00072
|View full text |Cite
|
Sign up to set email alerts
|

Acute Patellar Dislocation in Children and Adolescents: A Randomized Clinical Trial

Abstract: The long-term subjective and functional results after acute patellar dislocation are satisfactory in most patients. Initial operative repair of the medial structures combined with lateral release did not improve the long-term outcome, despite the very high rate of recurrent instability. A positive family history is a risk factor for recurrence and for contralateral patellofemoral instability. Routine repair of the torn medial stabilizing soft tissues is not advocated for the treatment of acute patellar disloca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
338
3
12

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 400 publications
(369 citation statements)
references
References 22 publications
(28 reference statements)
9
338
3
12
Order By: Relevance
“…Buchner et al [23], in their retrospective study, separate patients who underwent diagnostic arthroscopy and refixation of the osteochondral fragment into a special group from conservatively and surgically treated patients. Sillanpaa et al [14] add those patients to a group of nonoperatively treated patients, whereas the authors of randomised studies, Nikku et al [24], Palmu et al [22], and Christiansen et al [21], regard the procedure as diagnostic and therapeutic, which is mandatory prior to final selection of operative or nonoperative treatment. In our study, diagnostic arthroscopy with simultaneous management of the essential osteochondral fragment was regarded as an operative treatment that could accompany repair of medial parapatellar structures and/or lateral retinacular release, if necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Buchner et al [23], in their retrospective study, separate patients who underwent diagnostic arthroscopy and refixation of the osteochondral fragment into a special group from conservatively and surgically treated patients. Sillanpaa et al [14] add those patients to a group of nonoperatively treated patients, whereas the authors of randomised studies, Nikku et al [24], Palmu et al [22], and Christiansen et al [21], regard the procedure as diagnostic and therapeutic, which is mandatory prior to final selection of operative or nonoperative treatment. In our study, diagnostic arthroscopy with simultaneous management of the essential osteochondral fragment was regarded as an operative treatment that could accompany repair of medial parapatellar structures and/or lateral retinacular release, if necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, primary surgery to the medial parapatellar aspect is focused on reconstructing the MPFL and surrounding soft tissues. On the other hand, the tendency towards immediate lateral retinacular release (LRR) [20] in the aforementioned studies is controversial: from "never" [21], through "in selected cases" [10,11,22], to "always" [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Patellar tilt and translation can be measured on MRI or CT images (taken with the knee extended and the quadriceps contracted or relaxed) [7]. Although non-operative treatment remains the gold standard of treatment after primary patellar dislocation without osteochondral fragments [8][9][10], recurrent dislocations in this population may benefit from surgical intervention. Reconstruction of the MPFL prevents lateral patellar dislocation, reporting good results in the treatment of children [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…For acute patellar dislocation in children and adolescents, a 2008 study by Palmu et al demonstrated no improved longterm benefits to acute operative repair compared with non-operative management, and advocated against routine operative repair of the torn medial stabilizing soft tissues for the treatment of acute patellar dislocation in children and adolescents. 2 …”
Section: Introductionmentioning
confidence: 99%